Effects of the COVID-19 pandemic on sexual functioning and activity: a systematic review and meta-analysis - Mojgan Masoudi; Raziyeh Maasoumi; Nicola Luigi Bragazzi (BMC, 2022)
Abstract Background Since December 2019, when it was first reported in Wuhan, province of Hubei, China, the new virus SARS-CoV-2 has spread rapidly around the world and has become a global pandemic. During the COVID-19 pandemic, due to the public health measures implemented, people's sexual activity has also been affected. Restrictions on people's activities, reduced sports activities, economic issues, increased psychological stress, and reduced entertainment have, indeed, dramatically impacted sexual activity and functioning. The purpose of this study was tosystematically identify, collect and summarize the existing body of evidence from published studies on the effects of COVID-19 pandemic on sexual activity and functioning. Methods Several scholarly databases, namely MEDLINE (via PubMed interface), Web of Science (WOS), Embase, CINAHL, the Cochrane Library, Scopus, and PsycINFO databases, were mined from December 2019 to the end of January 2021. We utilized a random-effect meta-analytical model to analyze all the data. More in detail, the Standardized Mean Difference (SMD) was used in order to estimate and evaluate the effects of the COVID-19 pandemic on sexual activity and functioning. Results Twenty-one studies were included in the present study. In total, 2454 women and 3765 men were evaluated. In the present meta-analysis, sexual functioning and activity were assessed by means of two standardized and reliable tools, namely the "Female Sexual Function Index" (FSFI) and the "International Index of Erectile Function-5 items" (IIEF-5). A total of 5 studies reported the FSFI score before and after the COVID-19 pandemic in female participants. Based on the random-effect model, the SMD was computed to be − 4.26 [95% confidence interval or CI: − 7.26, − 1.25], being statistically significant. A total of 3 studies reported the IIEF-5 score before and after the COVID-19 pandemic in male participants. Based on the random-effect model, the SMD was computed to be − 0.66 [CI 95%: − 0.99, − 0.33], being statistically significant. In the majority of these studies, participants reported a reduction in the number of sexual relations and an increase in the frequency of solo sex activity, especially masturbation, compared to the time prior to the COVID-19 pandemic. Conclusion The results of the present study showed that COVID-19 related restrictions were correlated with higher rates of sexual dysfunction and reduced sexual activity; however, results of the current meta-analytical study show that this change in sexual functioning was greater in women compared to men. Sex is one of the dimensions of every person's life; therefore, researchers should identify the factors that lead to sexual dysfunction due to COVID-19 pandemic in their community. In this regard, sexologists should design and implement effective programs to reduce the heterogeneous causes affecting sexual functioning, given the psychological strain that the COVID-19 pandemic puts on individuals.